ANALISIS KARAKTERISTIK DAN PEMODELAN KEBUTUHAN PARKIR KENDARAAN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - oktaviani, Oktaviani; Ashar, Faisal; Dwi Laksana, Putra (Lembaga Penelitian Universitas Negeri Padang, 2009)
The increasing number of academics on Faculty of Engineering, State University of Padang (FT-UNP) resulted in the provision of facilities parking space problem. This study aims to determine the characteristics of parking, how parking demand model and know the standards required parking. Data space requirements include primary data obtained from field surveys used to obtain the characteristics of the parking and secondary data obtained from the Bureau of Academic and Student Affairs Administration FT-UNP. Parking demand modeling performed by the method of simple linear regression analysis. Independent variables that are reviewed include: the number of FT-UNP academic community. While the dependent on variable is the highest accumulation of parking and parking accumulation on average. The analysis showed that, the car is a vehicle with the highest accumulation index 1.24, and accumulated an average of 0.71, the highest accumulation on motorcycle accumulated an average of 1.02 0.59. Model the relationship between the accumulation of a car park with the highest number of academic community is y = 11.987 + 0.008 x (R2 = 0.919) and accumulated an average of y = 11.717 + 0.005 x (R2 = 0.904). While the motorcycle to the highest accumulation of y = -12.812 + 0.096 x (R2 = 0.966) accumulated an average y = -18.793 + 0.065 x (R2 = 0.952). To determine the vehicle parking space requirements based on the number of the academic community in the year 2010 (5721 people) are: 58 parking lot (SRP) for car or 725 m2, and for motorcycle parking lot 536 or 750 m2. Key words : Ferroelektrik, BST, Spin Coating.